Quality Assessment of Milk Powders Packed in Sudan - El Khier, Murwan Khalid Sabah; A. Yagoub, Abu El Gasim (Pakistan Journal of Nutrition, 2009)
Physicochemical, microbiological and sensory characteristics of milk powders packed in Sudan were investigated and compared with international quality standards. The compositions (moisture, fat, protein, ash and lactose) of the locally packed milk powders are almost insignificantly different (p